Benign Multicystic Peritoneal Mesothelioma (BMPM) as a rare cause of abdominal pain in a young male: case report and review of the literature. Issue 3 (13th March 2019) - Gussago, S; Spina, P; Guerra, A
Abstract: Benign Multicystic Peritoneal Mesothelioma (BMPM) is a rare benign cystic neoplasm that arise from the peritoneum, typically found in young females (83%), with a high incidence of local recurrence after resection (almost 50% of cases). Fewer than 200 cases have been reported worldwide in 2017. Due to its rarity and the lack of a classical clinical presentation, the diagnosis pre-operatively is challenging; moreover a great part of the literature is composed of case reports and small group studies. Nowadays, guidelines are still not available, and treatment is en bloc resection of the lesion. Some authors suggest the use of Hyperthermic Intraperitoneal Chemotherapy (HIPEC) associated with the surgical approach, even if comparative data on recurrence and complications are lacking. We report a case of BMPM diagnosed in a 40-year-old male who underwent an exploratory laparoscopy and complete excision of the neoformation. Pathology confirmed the presence of a BMPM.